Institusi Inklusif Primum Non Nocere Kesejahteraan Sosial - Dadang Hartanto (PERSPEKTIF, 2020)
The institutional model that works in a country in economic and political aspects influences social welfare. In the inclusive institutional model the principle that must be held is primum non necere or fisrt do no harm for social welfare. Proponents of the state must not suffer the lives of their people. In this paper it is reinforced that politics and economics are two sides of a coin that encourage and influence social welfare. Inclusive institutions always deal with extractive institutions. Daron Acemogle and James A. Robinso (2012) in their book Why Nations Fails reveal that economic growth and prosperity are associated with inclusive economic and political institutions, while extractive institutions typically lead to stagnation and poverty. Indonesia has the opportunity to have extractive institutions and therefore must be prevented by implementing democracy seriously and independent law enforcement based on due process of law. Inclusive institutions must be realized so that Indonesia can become a healthy and strong country. One of the health and strength of a country is determined by its economic strength which contributes to development and fiscal strengthening. Fiscal is built one of them by increasing tax revenue because of the contribution of taxation to the fiscal average of 77.6%